Use of GeoGebra in primary math education: a theoretical approach - Žilinskienė, Inga (Lietuvos matematikos rinkinys, 2014)
GeoGebra as cost-free, multi-platform mathematics software, dynamically connecting concepts in geometry, algebra and calculus is applied in different school’s levels, and primary school is no exception. The aim of the paper is to present a theoretical approach of application of GeoGebra in Lithuanian’s primary math education. It analyzes features of GeoGebra, its possible integration into primary school education according to Educational Plan and Programme. Also some examples how this software can be effectively incorporated into teaching and learning are presented. With a view to evaluate GeoGebra’s suitability to primary education primary school teachers were interviewed and results of that exploratory study are presented. Also the study seeks to identify the conditions to successfully support teachers in using GeoGebra and learning objects prepared by it in their teaching process including organisational and technical support required.